Interaction effect of obstructive sleep apnea and periodic limb movements during sleep on heart rate variability. (26th May 2019) - Li, Xiao; Covassin, Naima; Zhou, Junying; Zhang, Ye; Ren, Rong; Yang, Linghui; Tan, Lu; Li, Taomei; Xue, Pei; Tang, Xiangdong
Summary: We aimed at assessing cardiac autonomic function by heart rate variability during sleep in patients with obstructive sleep apnea and periodic limb movements during sleep, and to compare it with that of patients with obstructive sleep apnea only, periodic limb movements during sleep only, and controls. We also aimed at investigating the interaction effect between apnea–hypopnea index and periodic limb movement index on heart rate variability. Four groups of patients ( n = 42 each, total = 168) were identified based on the presence/absence of obstructive sleep apnea and periodic limb movements during sleep: + obstructive sleep apnea/− periodic limb movements during sleep (5 ≤ apnea–hypopnea index < 30 events per hr), − obstructive sleep apnea/+ periodic limb movements during sleep (periodic limb movement index > 15 events per hr), + obstructive sleep apnea/+ periodic limb movements during sleep, − obstructive sleep apnea/− periodic limb movements during sleep (controls). All groups were matched for age, sex and body mass index. Time‐ and frequency‐domain heart rate variability measures were calculated over 5‐min periods of stable stage 2 non‐rapid eye movement sleep. In patients with both obstructive sleep apnea and periodic limb movements during sleep, LFnu and LF/HF ratio were higher than in those with obstructive sleep apnea only, periodic limb movements during sleep only, and controls, while HFnu was the lowest among the four groups. LFnu, HFnu and LF/HF ratio were significantly and independently associated with minimal oxygen saturation in the + obstructive sleep apnea/+ periodic limb movements during sleep group. There was a significant interaction effect between apnea–hypopnea index and periodic limb movement index on LF/HF ratio ( p = 0.038) in patients with obstructive sleep apnea. Patients with elevated apnea–hypopnea index and elevated periodic limb movement index exhibited higher sympathovagal balance compared with those with high apnea–hypopnea index and low periodic limb movement index, and compared with those with low apnea–hypopnea index (regardless of periodic limb movement index). Increased sympathetic activation and decreased parasympathetic control appear to be related to the severity of oxygen desaturation. Apnea–hypopnea index and periodic limb movement index had interactive effects on increased sympathovagal balance in patients with obstructive sleep apnea.